Transcriptome Analysis Reveals Common and Differential Response to Low Temperature Exposure Between Tolerant and Sensitive Blue Tilapia (Oreochromis aureus) - Nitzan, Tali; Kokou, Fotini; Doron-Faigenboim, Adi; Slosman, Tatiana; Biran, Jakob; Mizrahi, Itzhak; Zak, Tatyana; Benet, Ayana; Cnaani, Avner (Frontiers in Genetics, 2019)
Tilapias are very important to the world’s aquaculture. As befitting fish of their tropical origin, their distribution and culture practices are highly affected by low temperatures. In this study, we used genetic and genomic methodologies to reveal pathways involved in the response and tolerance of blue tilapia (Oreochromis aureus) to low temperature stress. Cold tolerance was characterized in 66 families of blue tilapia. Fish from cold-tolerant and cold-sensitive families were sampled at 24°C and 12°C, and the transcriptional responses to low-temperature exposure were measured in the gills and liver by high-throughput mRNA sequencing. 494 genes displayed a similar temperature-dependent expression in both tolerant and sensitive fish and in the two tissues, representing the core molecular response to low temperature exposure. KEGG pathway analysis of these genes revealed down-regulation of focal-adhesion and other cell-extracellular matrix (ECM) interactions, and up-regulation of proteasome and various intra-cellular proteolytic activities. Differential responses between cold-tolerant and cold-sensitive fish were found with genes and pathways that were up-regulated in one group and down-regulated in the other. This reverse response was characterized by genes involved in metabolic pathways such as glycolysis/gluconeogenesis in the gills and biosynthesis of amino-acids in the liver, with low temperature down-regulation in tolerant fish and up-regulation in sensitive fish.